3D Bioprinting a human iPSC-derived MSC-loaded scaffold for repair of the uterine endometrium. (15th October 2020) - Ji, Wanqing; Hou, Bo; Lin, Weige; Wang, Linli; Zheng, Wenhan; Li, Weidong; Zheng, Jie; Wen, Xuejun; He, Ping
Abstract: Common events in the clinic, such as uterine curettage or inflammation, may lead to irreversible endometrial damage, often resulting in infertility in women of childbearing age. Currently, tissue engineering has the potential to achieve tissue manipulation, regeneration, and growth, but personalization and precision remain challenges. The application of "3D cell printing" is more in line with the clinical requirements of tissue repair. In this study, a porous grid-type human induced pluripotent stem cell-derived mesenchymal stem cell (hiMSC)-loaded hydrogel scaffold was constructed using a 3D bioprinting device. The 3D-printed hydrogel scaffold provided a permissive in vitro living environment for hiMSCs and significantly increased the survival duration of transplanted hiMSCs when compared with hiMSCs administered locally in vivo . Using an endometrial injury model, we found that hiMSC transplantation can cause early host immune responses (the serological immune response continued for more than 1 month, and the local immune response continued for approximately 1 week). Compared with the sham group, although the regenerative endometrium failed to show full restoration of the normal structure and function of the lining, implantation of the 3D-printed hiMSC-loaded scaffold not only promoted the recovery of the endometrial histomorphology (endometrial tissue and gland regeneration) and the regeneration of endometrial cells (stromal cells and epithelial cells) and endothelial cells but also improved endometrial receptivity functional indicators, namely, pinopode formation and leukemia inhibitory factor and αvβ3 expression, which partly restored the embryo implantation and pregnancy maintenance functions of the injured endometrium. These indicators were significantly better in the 3D-printed hiMSC-loaded scaffold group than in the unrepaired (empty) group, the hiMSCs alone group and the 3D scaffold group, and the empty group showed the worst repair results. Our study confirm that the 3D-printed hiMSC-loaded hydrogel scaffold may be a promising material for endometrial repair. Graphical abstract: Image, graphical abstract